2014
DOI: 10.1097/qco.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Update on the burden of Campylobacter in developing countries

Abstract: Purpose of review Recent work has added to the understanding of the burden of Campylobacter jejuni, C. coli, and non-jejuni/coli Campylobacter strains in children living in the developing world. Recent findings New diagnostic modalities and carefully-designed field studies are demonstrating that the burden of Campylobacter diarrhea in children in the developing world has been greatly underestimated. Furthermore, there is emerging recognition of an association between Campylobacter infection and malnutrition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 64 publications
4
110
2
4
Order By: Relevance
“…New diagnostic tools such as enzyme immunoassay (EIA) and molecular tests have shown a much higher positive rate of Campylobacter infection than found by culture 26 . Most laboratories use selective culture techniques for isolation of Campylobacter jejuni and C. coli , which led to the thought that they are the primary species associated with gastroenteritis.…”
Section: Emerging Molecular Diagnostic Toolsmentioning
confidence: 99%
“…New diagnostic tools such as enzyme immunoassay (EIA) and molecular tests have shown a much higher positive rate of Campylobacter infection than found by culture 26 . Most laboratories use selective culture techniques for isolation of Campylobacter jejuni and C. coli , which led to the thought that they are the primary species associated with gastroenteritis.…”
Section: Emerging Molecular Diagnostic Toolsmentioning
confidence: 99%
“…Research with C. jejuni has been challenging due to the high degree of genomic plasticity and high rates of genetic transformation found within this naturally competent microorganism (149). However, strains that carry or overexpress flagellum genes, adherence structures, and invasion mechanisms are associated with increased virulence (148)(149)(150)(151). As summarized below, pathogenic studies reveal that bile exposure acts as a stimulus for the upregulation of many virulence mechanisms in C. jejuni.…”
Section: Campylobacter Jejunimentioning
confidence: 99%
“…(41,42) In a 10-year study in Switzerland (from 2002 to 2012) the prevalence of Campylobacter in animals was indicated and it has been found that chicken are the most common reservoir/source of Campylobacter infection, with average contamination of 70.9%, whereas cattle have been named as the second most common source, with a rate of 19.3%, while dogs and pigs were other sources with rates of 8.6% and 1.2% respectively. (11) The presence of Campylobacter species as normal flora in stool and eggs of poultry is one of the major causes that might affect the prevalence of campylobacteriosis in patients. (38) Also there are some reports that found this pathogen in the normal flora of other animals.…”
Section: Discussionmentioning
confidence: 99%
“…(10) Environmental contamination can be caused by domestic animals and poultry (as natural reservoirs of Campylobacter species). (11) Poultry carcasses in stores that are not under sanitary monitoring and consumption of undercooked poultry meat are important causes of outbreaks. (12) The occurrence of this disease is usually higher in older persons over 75 years of age, young children under 4 years of age and young adults who are 20-40 years old.…”
Section: Original Article Introductionmentioning
confidence: 99%